Radiation-induced Bullous Lichen Planus: An Isomorphic Manifestation of Radiotherapy - Paul Cirotteau; Philippine Lucas; Léa Dousset; Valérie Cales; Olivier Gilliot; Thomas Jouary (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)